Carl Schmitt's institutional theory : the political power of normality / Mariano Croce, Andrea Salvatore. - Croce, Mariano; Salvatore, Andrea (Cambridge University Press, 2022)
In 1922, Carl Schmitt penned Political Theology, the celebrated essay in which he elaborated on the notorious theory that the heart of politics lies in the sovereign power to issue emergency measures that suspend the legal order. Ever since, Schmitt's thinking has largely been identified with this concept, despite him renouncing it over time. Offering a comprehensive analysis of Schmitt's writings, Carl Schmitt's Institutional Theory provides an ambitious, novel perspective on Carl Schmitt and his legal and political thinking. By delving into Schmitt's output over his decades-long career, Mariano Croce and Andrea Salvatore explore Schmitt's varied and developing thoughts on exceptionalism, societal pluralism and the law as the progenitor and enforcer of normality. Challenging dominant interpretations, Croce and Salvatore dethrone the false centrality of certain key texts, and instead provide a more unified, coherent account of his institutional theory from across his long and controversial career.